Dakelh materials, ACLS collection - Teit, James Alexander, 1864-1922 (1910)
The Dakelh (Carrier) materials in the ACLS collection consist of one item in the "Carrier" section of the finding aid: "Notes on various Athabaskan languages," recorded by James Teit, which partially includes Carrier vocabulary.